Reconstructing herbivore diets: a multivariate statistical approach to interpreting amino acid nitrogen isotope values - Chen, MHY; Kendall, IP; Evershed, RP; Bogaard, A; Styring, AK (Springer Nature, 2023)
Recent studies have demonstrated that there exists significant variability in amino acid (AA) δ15N values of terrestrial plants, discriminating among plant types (i.e., legume seeds, grasses, tree leaves) as well as tissues of the same plant. For the first time, we investigate the potential of the spacing between the δ15N values of different AAs to differentiate between plant types and thus elucidate their relative importance in herbivore diet. Using principal component analysis, we show that it is possible to distinguish among five plant categories—cereal grains, rachis, legume seeds, herbaceous plants, and woody plants—whose consumption has different implications for understanding herbivore ecology and management practices. Furthermore, we were able to correctly classify the herbaceous plant diet of modern cattle using AA δ15N values of their tooth dentine adjusted for trophic enrichment. The AA δ15N patterns of wild and domestic herbivores from archaeological sites seem to be consistent with diets comprised predominantly of herbaceous plants, but there is variation in AA δ15N values among individuals that may reflect differing inputs of other plant types. The variation in AA δ15N values does not necessarily reflect the variation in herbivore bulk collagen δ13C and δ15N values, indicating that AA δ15N values have the potential to provide additional insights into plant dietary sources compared to bulk tissue isotope values alone. Future work should focus on defining trophic enrichment factors for a wider range of terrestrial herbivores and expanding libraries of primary producer AA δ15N values.